2007
DOI: 10.1186/1479-5876-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sulfate and Platelet-Rich Plasma make a novel osteoinductive biomaterial for bone regeneration

Abstract: BackgroundWith the present study we introduce a novel and simple biomaterial able to induce regeneration of bone. We theorized that nourishing a bone defect with calcium and with a large amount of activated platelets may initiate a series of biological processes that culminate in bone regeneration. Thus, we engineered CS-Platelet, a biomaterial based on the combination of Calcium Sulfate and Platelet-Rich Plasma in which Calcium Sulfate also acts as an activator of the platelets, therefore avoiding the need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 41 publications
2
57
0
4
Order By: Relevance
“…La materia prima de la que se hace es relativamente barata y abundante, se puede combinar con otros materiales como autoinjertos, aloinjertos, fosfatos de calcio, y vidrios bioactivos, para aumentar sus propiedades de unión, el volumen y la eficacia de los injertos óseos. También ha servido como un material de vehículo excelente para los factores de crecimiento y múltiples drogas, a pesar de estas ventajas, el material no ha gozado de la popularidad de muchos otros materiales de regeneración, aunque recientemente ha recibido una atención renovada con propiedades hemostáticas, angiogénicas y de barrera o membrana para la preservación de rebordes alveolares postexodoncias (1)(2)(3)(4)(5)(6)(7)(8) . …”
Section: Introductionunclassified
“…La materia prima de la que se hace es relativamente barata y abundante, se puede combinar con otros materiales como autoinjertos, aloinjertos, fosfatos de calcio, y vidrios bioactivos, para aumentar sus propiedades de unión, el volumen y la eficacia de los injertos óseos. También ha servido como un material de vehículo excelente para los factores de crecimiento y múltiples drogas, a pesar de estas ventajas, el material no ha gozado de la popularidad de muchos otros materiales de regeneración, aunque recientemente ha recibido una atención renovada con propiedades hemostáticas, angiogénicas y de barrera o membrana para la preservación de rebordes alveolares postexodoncias (1)(2)(3)(4)(5)(6)(7)(8) . …”
Section: Introductionunclassified
“…293,294 The application of PRP in cartilage repair is relatively new, and there are limited in vivo studies regarding its use for that specific application. However, it has been shown that PRP stimulates chondrocyte and MSC proliferation and cartilage ECM synthesis of proteoglycans and collagen type II.…”
Section: (2011)mentioning
confidence: 99%
“…72 PRP kullanımının; genç hastalardan kan alma zorluğu, özel ekipman ve PRP belirteci gerektirmesi gibi dezavantajları bulunmaktadır. 7 PRP, sığır trombini veya kalsiyum sülfatla aktive edilmektedir, 73 ancak sığır trombininin hemoraji, tromboz ve sistemik lupus eritomatozus (SLE) gibi önemli immün reaksiyonlara sebep olduğu bildirilmektedir. 74 Bu nedenle, son zamanlarda gerçekleştirilen çalışmalarda sığır trombininin olumsuz etkilerinden dolayı PRP'yi aktive etmek için kalsiyum sülfat kullanılmaktadır.…”
unclassified
“…74 Bu nedenle, son zamanlarda gerçekleştirilen çalışmalarda sığır trombininin olumsuz etkilerinden dolayı PRP'yi aktive etmek için kalsiyum sülfat kullanılmaktadır. 73 Torabinejad ve ark. 75 11 yaşındaki hastanın ekstrüze olan ve hemen replante edilen ancak pulpal nekroz ve apikal periodontitis gözlenen üst çene ikinci küçük azı dişine % 5,25 NaOCl ile irige ettikten sonra ÜAP uygulamışlardır.…”
unclassified